Current Trends in Short- and Long-period Fiber Gratings - Cuadrado-Laborde, Christian (IntechOpen, 2013)
In this book the reader will find a collection of chapters written by different experts around the world, describing the current research trends in both short- and long-period fiber grating technology. This work is mainly addressed to researchers already working in this area, but it is also accessible to anyone with a scientific background who desires to have an updated overview of the recent progress in this domain. It will also be valuable to scientist and engineers who have become newly involved in this field. Each chapter is self-contained and can be read independently of the others. This book intends to provide highlights of the current research in this area, showing the recent advances in the field of fiber gratings.